A case of cirsoid aneurysm: Case report - Jolly Sinha; Avdhesh Shukla; Vivek Kumar Kankane; Avinash Sharma; Kundan Kumar (Asian Journal of Medical Sciences, 2024)
Scalp cirsoid aneurysm is an arteriovenous fistula of the scalp that is usually unconnected by intracranial or cerebral vessels. Variceal dilatation of draining veins can produce cosmetic concerns, masses, local pain, palpable thrills, audible bruits, headache, tinnitus, and torrential hemorrhage. Its etiopathogenesis is not well understood. Treatment includes surgery (fistula repair by simple surgical ligation until gross total resection), embolization (whether percutaneous or endovascular), or a combination of the two. Here is a case report of a 40-year-old male patient who had right superficial temporal artery cirsoid aneurysm who underwent surgical ligation with complete excision of the lesion.